2016
DOI: 10.4251/wjgo.v8.i2.165
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in treatment and diagnosis of pancreatic cancer with radiopharmaceuticals

Abstract: Pancreatic cancer (PC) is a major health problem. Conventional imaging modalities show limited accuracy for reliable assessment of the tumor. Recent researches suggest that molecular imaging techniques with tracers provide more biologically relevant information and are benefit for the diagnosis of the cancer. In addition, radiopharmaceuticals also play more important roles in treatment of the disease. This review summaries the advancement of the radiolabeled compounds in the theranostics of PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Molecular tracers such as F-fluorodeoxyglucose used in positron emission tomography (PET) and CT imaging hold promise as a powerful diagnostic tool for potentially malignant tumours, although a high false-positive rate in hyperglycaemic patients must be addressed [10]. …”
Section: Current Shortcomings In the Diagnosis And Treatment Of Pancrmentioning
confidence: 99%
“…Molecular tracers such as F-fluorodeoxyglucose used in positron emission tomography (PET) and CT imaging hold promise as a powerful diagnostic tool for potentially malignant tumours, although a high false-positive rate in hyperglycaemic patients must be addressed [10]. …”
Section: Current Shortcomings In the Diagnosis And Treatment Of Pancrmentioning
confidence: 99%
“…However, 18 F-FDG PET/CT still has several drawbacks in detecting pancreatic cancer. The chronic and acute pancreatitis both have high 18 F-FDG uptake, leading to false-positive interpretations, and the application of 18 F-FDG PET in hyperglycemic patients also is not ideal, because the uptake of imaging agent is suppressed as a result of high serum glucose competitive inhibition 5 , 6 . Therefore, the development of new molecular probes, which can target pancreatic cancer specifically and overcome the limitations of 18 F-FDG to some extent, are urgently needed and have great clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is considered one of the most aggressive and fatal malignant gastrointestinal tract tumors, and its morbidity and mortality rates are gradually increasing [ 1 ]. Even with improved diagnostic strategies and the best therapeutic intervention available today, the 5-year survival rate for the patients remains alarmingly dismal, at less than 5% [ 2 , 3 ]. The latest epidemiological investigation showed that pancreatic cancer accounts for 3% of cancer-related deaths worldwide, making it the 7 th most common cause of death induced by cancer worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%